The remarkable impact of renewable energy generation in Sicily onto electricity price formation in Italy. Issue 3 (18th May 2016) - Meneguzzo, Francesco; Ciriminna, Rosaria; Albanese, Lorenzo; Pagliaro, Mario
Abstract: During the first half of 2015, for the first time, the zonal electricity price in Sicily decreased below than the national wholesale price in Italy. Showing the unique pattern of electricity consumption in Italy's largest region at different time scales, we identify the effectiveness of the impact of renewable power generation on utility‐scale in Sicily upon the whole of Italy's electricity market. Increasing the electrification of the energy end uses, as it is happening despite prolonged reduction in electricity demand, will lead to further benefits for power consumers throughout the whole country. Abstract : Showing the unique pattern of electricity consumption in Italy's largest region, we identify the effectiveness of the impact of renewable power generation on utility‐scale in Sicily upon the whole of Italy's electricity market.